Species composition and stand structure of myrtaceae trees in a lower montane forest at Fraser Hill, Selangor - Zohari, Ahmad Fitri; Nik Hashim, Nik Hazlan; Nik Ali, Nik Norafida; Mustafa Bakray, Nur ‘Aqilah; Zulkifli, Mohammad Khairul Faizi; Zainuddin, Ahmad Firdaus; Wan Ismail, Wan Norilani; Engku Ariff, Engku Azlin Rahayu; Kusin, Mazlin; Mohamad, Norazlinda; Abd Rasid, Khairunnisaa; Mohamad, Abdul Latiff (Universiti Teknologi MARA (UiTM), 2024)
This research aimed to ascertain the species composition and stand structure of Myrtaceae trees in a lower montane forest at Fraser's Hill, Selangor. A total of nine species and two genera of Myrtaceae from 22 individuals for trees with diameter ≥ 5.0 cm DBH were recorded in the study plot of 0.2 ha. Syzygium is the most diverse genus, with eight species, whereas Rhodamnia consists of only one species. The tree's DBH range is between 5.0 and 32.0 cm. The density of Myrtaceae is 110 individuals/ha. Syzygium is also the densest genus, with 95 individuals/ha, whereas Syzygium sp. 12 has the densest species, with 45 individuals/ha. The total basal area for Myrtaceae is 1.74 m2/ha, while Syzygium contributed 95.68 % of the basal area with 1.67 m2/ha. Syzygium sp. 12 contributed the highest basal area of 1.13 m2/ha (65.12%). Syzygium oreophium is an endemic species to Peninsular Malaysia. Another four species, namely Syzygium griffithii, S. rugosum var. cordatum, S. syzygoides, and Syzygium sp. 12, are considered new records for Fraser Hill